The Effects of Multimedia Learning and Vocabulary Mastery on Students’ Japanese Reading Skills - Haryono Haryono (Lingua Cultura, 2016)
The objective of this research was to determine the effects of multimedia learning and vocabulary mastery on students’ Japanese Reading skills which used two-way treatment experiment design. This research was conducted at The Japanese Language Program, Faculty of Humanities – UNSOED with 48 students as the sample. The method used in this study was an experimental method with treatment by level 2 x 2 design. The formulation of this research was the effect of Rosetta Stone and Tell Me More Japanese multimedia learning against Japanese reading skill and the effect of vocabulary (high and low) to the Japanese reading skills. The results of this study are students’ Japanese reading skills presented by “Rosetta Stone” is better than those presented by “Tell Me More Japanese”. There are any effects of interaction among multimedia learning and vocabulary mastery on students’ Japanese Reading skills. Besides that, students’ Japanese Reading skills who have high-level vocabulary mastery and presented by “Rosetta Stone” is better than those presented by “Tell Me More Japanese”. Then, students’ Japanese Reading skills who have low-level vocabulary mastery and presented by “Tell Me More Japanese” is better than those presented by “Rosetta Stone”.